IMPLEMENTATION OF PARALLEL PROGRAMMING ON MULTICORE PERSONAL COMPUTERS - Іванова, Л.; Чистяков, О.; Іслямова, І. (Science-based technologies, 2010)
Is conducted the experimental research of application of a software OpenMP for multisequencing the programs on multinuclear personal computers with the purpose of increase of their productivity at problem solving.